IMPLEMENTING POWTOON TO IMPROVE STUDENTS’ INTERNATIONAL CULTURE UNDERSTANDING IN ENGLISH CLASS - Lulud Oktaviani; Berlinda Mandasari; Reynita Adlina Maharani (Universitas Teknokrat Indonesia, 2020)
The use of technology has increased rapidly in our daily activities since first industrial revolution and its features also becomes more and more enchanting from time to time. Thus, people are used to work with it to lighten their jobs, including education, such as delivering/learning material through multimedia, online teaching and learning, etc. It is line with the result of preliminary study that 56% students of English Literature at Universitas Teknokrat Indonesia (UTI) said their lecturers used more technology in class. Thus, the researchers used classroom action research in order to know whether the use of technology does not only help the lecturer in delivering material in a class but also improve students’ international culture understanding in English class. To collect the data, the researchers used observations, tests, and questionnaires. The subjects of this research were second semester students of English Literature at UTI. The finding showed that students’ international culture understanding improved after each cycle. Improvement was also seen based on the result of observations that students showed positive behaviour during the teaching and learning activity.